Time-resolved x-ray diffraction study of ultrafast acoustic phonon dynamics in Ge/Si-heterostructures - Sokolowski-Tinten, K; Cavalleri, A; Siders, C; Brown, F; Leitner, D; Toth, C; Kammler, M; von Hoegen, M; von der Linde, D; Squier, J; Barty, C; Wilson, K (2001)
Using time-resolved x-ray diffraction the ultafast strain dynamics in fs-laserexcited Ge/Si-heterostructures has been studied. A fluence dependent, anharmonic damping of the impulsively generated acoustic phonons and vibrational transport across the buried Ge/Si-interface are observed.